The Unfinished Museum: The Case of Pasargadae World Heritage Site Museum - Mozaffari, Ali; Westbrook, N. (Published for the Society of Architectural Historians Australia and New Zealand (SAHANZ), 2011)
This paper examines, for the first time, the problem of an unfinished site museum in the World Heritage Site of Pasargadae in Iran. Pasargadae was constructed as the capital of Cyrus the Great, the founder of the Achaemenid dynasty in 500 BCE. Sources have suggested that at this location Cyrus defeated his opponent, the leader of the Medes, uniting the Persians and the Medes and launching the multi-ethnic Achaemenid (550-330 BCE) Empire. The site, which included royal tombs, palace structures and gardens and a citadel, was revered by the Persians. In the twentieth century, the site and its iconic structure, Cyrus's tomb, were colligated into nationalist ideology. In 1971, it became one of the key locations for the Celebration of 2500th anniversary of Persian Kingship by the last Pahlavi monarch Mohammad Reza Pahlavi. In the early 1970s, a site museum was commissioned. Constructed commenced, but was unfinished at the time of the Islamic Revolution of 1979 and the building remains as a 'modern ruin'. In 2004, Pasargadae was listed as a World Heritage site since it represents an origin for Perso-Islamic gardens, an original interview with its architect, Hossein Amanat, to contextualize and historicise it as an architectural fragment. Positing the museum as an instance of 'peripheral modernism', the paper argues for including this fragment as part of the World Heritage Site of Pasargadae.